Effectiveness of Postoperative Adjuvant Radiotherapy in Atypical Meningioma Patients After Gross Total Resection: A Meta-Analysis Study - He, Lingzhe; Zhang, Buyi; Zhang, Jianmin; Guo, Zhige; Shi, Feina; Zeng, Qiang (Frontiers in Oncology, 2021)
Background: It still remains unclear whether patients with atypical meningioma (AM) could benefit from postoperative adjuvant radiotherapy (PORT) after gross-total resection (GTR). Objective: Exploring the effectiveness of PORT on AM patients after GTR. Methods: Literatures on PubMed, Embase, Web of science and Scopus databases published between January 2000 and January 2019 were searched. After the selection based on the certain exclusion criteria, the Newcastle-Ottawa evaluation scale was used to evaluate the quality of the included literatures. Finally, a meta-analysis was conducted to analyze the effectiveness of PORT on local control (LC), progression-free survival (PFS) and overall survival (OS) in atypical meningioma patients after GTR. Results: A total of 17 articles with 2008 AM patients were included in the meta-analysis. The 5-year LC, 5-year PFS and 5-year OS rates were 82.2%, 84.1% and 79.0%, respectively, for AM patients receiving PORT after GTR, and they were 71.0%, 71.9% and 81.5%, respectively, for those not receiving PORT after GTR. PORT could significantly improve 5-year LC rate (OR [95% Cl] =2.59 [1.40 - 4.81], P = 0.001) and 5-year PFS rate (OR [95% Cl] = 1.99 [1.35 - 2.95], P = 0.001), but did not significantly improve 5-year OS rate (OR [95% Cl] = 1.22 [0.73 - 2.05], P = 0.454). Conclusion: PORT could improve the 5-year LC rate and 5-year PFS rate in AM patients after GTR. AM patients might benefit from PORT after GTR.